IMPLEMENTSI ETIKA BISNIS ISLAM DALAM PROSES PRODUKSI: STUDI KASUS PADA INDUSTRI UMKM BERKAH ABADI - muhammad noorhasan ulul abshor; Catur Wahyono (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze in depth the implementation of Islamic Business Ethics in the operations of Berkah Abadi, a micro, small and medium enterprise (MSME) located in Pacitan, East Java, and engaged in the snack chip production industry. Using a descriptive qualitative approach, this study collected data through in-depth interviews with the owners and employees of Berkah Abadi, as well as conducting observations of the production process and daily business interactions. The focus of the study is to identify and understand how the fundamental principles of Islamic Business Ethics, which include honesty in transactions and product information, fairness in relationships with suppliers and employees, trustworthiness in maintaining quality and customer trust, compliance with sharia in every aspect of finance and operations, social responsibility towards the surrounding community and the environment, and efforts to achieve ihsan in providing the best service and quality, are manifested in real terms in the business practices of Berkah Abadi MSME. The findings of this study indicate that Berkah Abadi not only makes Islamic Business Ethics a set of moral values, but also as an operational strategy integrated into its entire business value chain. The implementation of these principles contributes significantly to building a positive image of the company in the eyes of customers and the community, increasing the level of consumer trust in the products produced, strengthening good relationships with suppliers and employees, and creating an ethical and productive work environment. This study seeks to find out how compliance with Islamic values plays a role in creating blessings and sustainability of the Berkah Abadi MSME business amidst market competition. The impact of this study provides a model for the implementation of Islamic Business Ethics that can be emulated by other MSMEs, especially those operating in Indonesia, in an effort to build a business that is not only economically profitable, but also has a positive social and spiritual impact.